2015
DOI: 10.1021/acssuschemeng.5b00098
|View full text |Cite
|
Sign up to set email alerts
|

Production of Water-Soluble Hardwood Kraft Lignin via Sulfomethylation Using Formaldehyde and Sodium Sulfite

Abstract: Kraft lignin can be extracted from black liquor (i.e., spent liquor) of a kraft pulping process to produce value-added chemicals, but its limited water solubility hampers its end-use applications. The main objective of this study was to investigate the sulfomethylation of kraft lignin to produce water-soluble kraft lignin with an anionic charge density. In this work, hardwood kraft lignin was modified with formaldehyde and sodium sulfite under alkali conditions. The optimum conditions for sulfomethylation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 41 publications
5
90
0
Order By: Relevance
“…[103] Although an alkaline environment was necessary for the carboxyethylation reaction, it promoted the hydrolysis of LS. The experimentala nd modeling analyses confirmed that CELS with am aximum charged ensity of À3.56 meq g À1 , molecular weight of 46 493 gmol À1 ,a nd ad egree of substitution of 0.78 could be generated under the optimum conditions of 30 wt %N aOH, 2.0 mol mol À1 2-chloropropinic acid/lignosulfonates,9 0 8C, 0.5 h, and 0.03 mol of 2-chloropropinic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[103] Although an alkaline environment was necessary for the carboxyethylation reaction, it promoted the hydrolysis of LS. The experimentala nd modeling analyses confirmed that CELS with am aximum charged ensity of À3.56 meq g À1 , molecular weight of 46 493 gmol À1 ,a nd ad egree of substitution of 0.78 could be generated under the optimum conditions of 30 wt %N aOH, 2.0 mol mol À1 2-chloropropinic acid/lignosulfonates,9 0 8C, 0.5 h, and 0.03 mol of 2-chloropropinic acid.…”
Section: Discussionmentioning
confidence: 99%
“…[25,103] Hence,atotal of 16 runs was conducted based on Ta guchi orthogonal design (L 16 )t od etermine the optimum conditions to produce CELS with the maximumc harge density and molecular weight.T he selected reactionc onditions and polymerp roperties are given in Ta ble 3. [25,103] Hence,atotal of 16 runs was conducted based on Ta guchi orthogonal design (L 16 )t od etermine the optimum conditions to produce CELS with the maximumc harge density and molecular weight.T he selected reactionc onditions and polymerp roperties are given in Ta ble 3.…”
Section: Optimizationmentioning
confidence: 99%
“…In this process, kraft lignin was reacted at 0.80:1 (w/w) sodium sulfite/lignin and 0.12:1 (w/w)f ormaldehyde/lignin for 2h at 140 8Ct op roduce sulfomethylated lignin. [28] Alternatively,s ulfomethylated kraft lignin was proposed to be produced at am olar ratio of 1:0.9 lignin/ sodium hydroxymethyl sulfonate at 100 8Cf or 3h without cross-linking. [71] The product mayb ep urified by filtration.…”
Section: Sulfomethylationmentioning
confidence: 99%
“…[71] Formaldehyde was subsequently added at a0 .6:1 molarr atio of formaldehyde/lignin and furtherr eacted for 5hat 100 8Ca nd pH 7. [28] The benefito fr eactingw ith sodium hydroxymethyl sulfonate is to avoid two reactions tages, and to develop as imple process for producings ulfonated lignin, but, in this case, the molecularw eight of the product is low relative to that of the two-step process. The anionic charge density increased from 0t oÀ1.6 meq g À1 ,t he molecular weighti ncreased from about 22 700 to 53 400 gmol À1 ,a nd the sulfonate group content increased from 0.03 to 1.48 mmolg À1 .…”
Section: Sulfomethylationmentioning
confidence: 99%
See 1 more Smart Citation